Constant-amplitude fatigue behavior of M24 high-strength bolt of end-plate flange connection. (December 2021) - Jiao, Jinfeng; Liu, Zhanxiang; Guo, Qi; Liu, Yong; Lei, Honggang
Abstract: Investigating the fatigue performance of high-strength bolt is essential to prevent related accidents. An axial-tensile fatigue test under a stress ratio of 0.5 was performed on 21 specimens of high-strength bolts to investigate the constant-amplitude fatigue performance of grade 8.8 M24 high-strength bolts. Based on experimental results, S–N curves were obtained through regression analysis, and fractographic analysis was conducted on typical specimens. Moreover, the results were compared with the existing fatigue experimental results and standards. Further, a finite element model was established to analyze the stress distribution of the bolts. It was found that the fatigue strength of the high-strength bolt at 2 × 10 6 cycles under a stress ratio of 0.5 was 89.76 MPa, which is 1.60 to 1.87 times greater than the values specified in the current standards. Through the comparison of the fatigue tests under stress ratios of 0.3, 0.5, and 0.8, the fatigue strength decreased as the stress ratio increased. Additionally, two main fatigue failure modes were found, with most bolts fracturing at the root of the first loaded thread; this is confirmed by the stress concentration location obtained from finite element analysis. The fracture morphology of the bolts exhibited a single-point fatigue source and possessed obvious fatigue fracture characteristics. It was concluded that the area of the fatigue propagation region was basically inversely proportional to stress ratio.